Ronald L. Ziegler papers - Ziegler, Ronald L. (Ronald Louis), 1939-
Correspondence, memoranda, speeches, writings, political files, subject files, legal material, notes, briefing material, transcripts of press briefings and press conferences, press releases, calendars and schedules, telephone logs, biographical material, family papers, printed matter, clippings, photographs, and other papers pertaining chiefly to Ziegler's activities as White House press secretary, assistant to President Richard M. Nixon, and assistant to Nixon after his resignation from the presidency. Subjects include Republican Party activities in California during the 1960s, Nixon's 1968 presidential campaign, the press and press coverage, the Vietnam War, prisoners of war, Paris peace talks, Watergate Affair, Nixon's resignation and pardon, and foreign relations especially with China and the Soviet Union. Correspondents include Patrick J. Buchanan, Dwight L. Chapin, Ken W. Clawson, Julie Nixon Eisenhower, Franklin R. Gannon, David R. Gergen, Alexander Meigs Haig, H.R. Haldeman, Bruce A. Kehrli, Richard M. Nixon, David N. Parker, Diane Sawyer, Gerald Lee Warren, and J. Bruce Whelihan.
White House press secretary, assistant to President Richard M. Nixon, and trade association administrator.
Collection material in English, with Chinese and Russian.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Buchanan, Patrick J. -- 1938- -- Correspondence; Chapin, Dwight L. -- 1940- -- Correspondence; Clawson, Ken W. -- 1936-1999 -- Correspondence; Eisenhower, Julie Nixon -- Correspondence; Gannon, Franklin R. -- 1942- -- Correspondence; Gergen, David R. -- 1942- -- Correspondence; Haig, Alexander Meigs, -- 1924-2010 -- Correspondence; Haldeman, H. R. -- 1926-1993 -- Correspondence; Kehrli, Bruce A., -- 1944-1996 -- Correspondence; Nixon, Richard M. -- 1913-1994.; Nixon, Richard M. -- 1913-1994 -- Correspondence; Parker, David N., -- 1940- -- Correspondence; Sawyer, Diane, -- 1945- -- Correspondence; Warren, Gerald Lee, -- 1930- -- Correspondence; Whelihan, J. Bruce, -- 1942- -- Correspondence; Ziegler family; United States. -- Office of the White House Press Secretary; Republican Party (U.S. : 1854- ); Political corruption -- United States; Presidents -- Press coverage -- United States; Presidents -- United States -- Election -- 1968.; Prisoners of war; Vietnam War, 1961-1975.; Vietnam War, 1961-1975 -- Peace; Vietnam War, 1961-1975 -- Prisoners and prisons; Watergate Affair, 1972-1974.; California -- Politics and government -- 1951-; China -- Foreign relations -- United States; Soviet Union -- Foreign relations -- United States; United States -- Foreign relations -- 20th century; United States -- Foreign relations -- China; United States -- Foreign relations -- Soviet Union; United States -- Politics and government -- Press coverage; United States -- Politics and government -- 1969-1974.; Executives; Presidential assistants; Press secretaries